SPATIAL ANALYSIS OF LAND USE AND SHALLOW GROUNDWATER VULNERABILITY IN THE WATERSHED ADJACENT TO ASSATEAGUE ISLAND NATIONAL SEASHORE, MARYLAND AND VIRGINIA, USA - Lamotte A.E.; Greene E.A. (My University, 2007)
Spatial relations between land use and groundwater quality in the watershed adjacent to Assateague Island National Seashore, Maryland and Virginia, USA were analyzed by the use of two spatial models. One model used a logit analysis and the other was based on geostatistics. The models were developed and compared on the basis of existing concentrations of nitrate as nitrogen in samples from 529 domestic wells. The models were applied to produce spatial probability maps that show areas in the watershed where concentrations of nitrate in groundwater are likely to exceed a predetermined management threshold value. Maps of the watershed generated by logistic regression and probability kriging analysis showing where the probability of nitrate concentrations would exceed 3 mg/L (>0.50) compared favorably. Logistic regression was less dependent on the spatial distribution of sampled wells, and identified an additional high probability area within the watershed that was missed by probability kriging. The spatial probability maps could be used to determine the natural or anthropogenic factors that best explain the occurrence and distribution of elevated concentrations of nitrate (or other constituents) in shallow groundwater. This information can be used by local land-use planners, ecologists, and managers to protect water supplies and identify land-use planning solutions and monitoring programs in vulnerable areas.
Keywords: GROUNDWATER; GEOSTATISTICS; SPATIAL STATISTICS; LOGISTIC REGRESSION; PROBABILITY KRIGING